Analisis Kinerja Keuangan Bank Bjb Syariah Menggunakan Metode Risk Profile, Good Corporate Governance, Earning, Capital (RGEC) Periode 2017-2021 - Siti Nurjanah, Riski; Jalaludin, Jalaludin; Bahri, Saepul; Nurbaeti, Ayi (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Financial performance is a reflection of the success or failure of a bank in carrying out its operational activities. The measuring instrument for assessing a bank's financial performance which states whether or not a bank is healthy is described in detail in the provisions governing the bank's soundness level. In measuring the financial performance of a healthy bank or not, the ratio value is used. This research is motivated by the ratio with the predicate Very Healthy, healthy, quite healthy, less healthy and very unhealthy. The purpose of this study is to determine the financial performance of BJB Syariah Bank based on Risk Profile, Good Corporate Governance, Earning, Capital from 2017-2021. This research uses a descriptive qualitative approach using the measurement of the RGEC ratio. It can be concluded that the BJB Syariah bank has a BJB Syariah Health Level for the 2017-2021 period with the Risk Profile method (Risk Profile) consisting of NPF and FDR. NPF in 2017-2021 was in the range of 3.42 and 5.28 categorized as very healthy. FDR in 2017-2021 was in the range of 81.55 and 93.56 categorized as quite healthy. Good Corporate Governance of BJB Syariah for the 2017-2021 period is in the range 2 and 3 which is categorized as quite healthy. Earnings (profitability) consisting of ROA and NIM of BJB Syariah for the period 2017-2021 are in the range of 4,870 and 5,771 categorized as very healthy. The ROA of BJB Syariah for the 2017-2021 period is in the range of 0.4 and 0.10 which is categorized as unhealthy. BJB Syariah's capital for the 2017-2021 period is in the range of 14.95 and 24.14 which is categorized as very healthy. RGEC BJB Syariah for the period 2017-2021 is in the range of 71.99 categorized as healthy.